Reflecting the changing world of work? A critique of existing survey measures and a proposal for capturing new ways of working - Lott, Yvonne; Kelliher, Clare; Chung, Heejung (SAGE, 2022)
In recent decades we have seen significant and varied changes in the world of work. Most prominent among these is the diminishing prevalence of the standard employment relationship. These changes challenge traditional notions of what constitute ‘employment’, ‘employers’, ‘employees’, the ‘workplace’ and the ‘working day’. Many current survey instruments are still based on the concept of the standard employment relationship, however. This article illustrates some limitations of existing conceptualisations and definitions of flexible work arrangements and of the instruments used to measure them in major surveys. It also suggests ways of tackling these limitations. The aim of highlighting potential limitations of existing survey instruments is to enable data users to be more reflective about what the results actually do and do not report, and to encourage survey designers to modify existing instruments and develop new instruments to better capture contemporary realities, including multiple jobholding and internet and platform work.
Keywords: Conceptualisation; definition and measurement of flexible work arrangements; standard employment relationship; ‘normal’ work biography; multiple-job holding; internet and platform work; flexitime; working from home